Pengaruh Jumlah Penduduk, Tenaga Kerja, Dependency Ratio dan Rasio Jenis Kelamin terhadap PDRB di Kota Banjarmasin - Rafik Muhammad; Khairi Pahlevi (PPJP Universitas Lambung Mangkurat, 2020)
AbstractThe objectives in this study are (1) to determine the effect of population on GRDP in Banjarmasin City; (2) to assess the impact of labor on GRDP in the city of Banjarmasin; (3) to determine the effect of the ratio of dependents to GRDP in the town of Banjarmasin; (4) to assess the impact of sex ratio on GRDP in Banjarmasin City; (5) To find out the simultaneous influence of population, labor, dependency ratio, and sex ratio to GRDP in Banjarmasin City. And this research is expected to provide understanding to local governments, private parties, and community institutions with interest in economic development in the city of Banjarmasin through the GRDP and an overview of their population. This research can be a reference in the preparation of local government policies for economic development in Banjarmasin. This research method uses data collection methods by taking data from the central static and related agencies. After that, multiple linear regression analysis is performed to see the effect of independent variables on the dependent. The software used for regression analysis is Eviews. This study's research indicates that the population is having a significant impact and has a positive influence on the GRDP of the City of Banjarmasin; the workforce and the ratio of dependents do not substantially affect the GRDP of the City of Banjarmasin. While the sex ratio has a significant influence and is negatively related to GRDP.